Mauritania : Transforming the Jobs Trajectory for Vulnerable Youth - World Bank (World Bank, Washington, DC, 2018)
Poverty reduction and youth employment remain deeply intertwined in Mauritania. Mauritania’s job-related challenge is characterized by a low-growth macroeconomic context, high reliance on minerals and extractives, and marked poverty and social exclusion. With youth (15–24 year olds) comprising over 40 percent of the population as of 2014, they are particularly vulnerable to high social exclusion. The main objective of this policy note is to provide an overview of the jobs challenge in Mauritania, with a focus on constraints and opportunities facing youth over the short to long term. To this end, it assesses overarching youth employment trends and gaps and offers recommendations for facilitating their entry into good, productive jobs. The note analyzes policy options, risks, and opportunities for strengthening youth employment prospects over the short to long term, with a focus on active labor market programs within an integrated approach to diversification, job creation, and poverty reduction. Moving forward, stronger public-private coalitions lie at the heart of youth employment and social inclusion in Mauritania.